2021
DOI: 10.1177/0018720821992223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hearing and Head Protection on the Localization of Tonal and Broadband Reverse Alarms

Abstract: Objective This study explored the effects of hearing protection devices (HPDs) and head protection on the ability of normal-hearing individuals to localize reverse alarms in background noise. Background Among factors potentially contributing to accidents involving heavy vehicles, reverse alarms can be difficult to localize in space, leading to errors in identifying the source of danger. Previous studies have shown that traditional tonal alarms are more difficult to localize than broadband alarms. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
4
0
7
Order By: Relevance
“…Indeed, while the mean RMSEs were smallest for the front monitors when HPDs were not used, when HPDs were used, the mean RMSEs for the front monitors exceeded the mean RMSEs for the right and left monitors. Previous studies also found better localization with earplugs than earmuffs [4,7,8,34,37].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, while the mean RMSEs were smallest for the front monitors when HPDs were not used, when HPDs were used, the mean RMSEs for the front monitors exceeded the mean RMSEs for the right and left monitors. Previous studies also found better localization with earplugs than earmuffs [4,7,8,34,37].…”
Section: Discussionmentioning
confidence: 73%
“…Aside from testing additional types of HPDs with different attenuation spectra and levels, testing different types of speech stimuli is also necessary, particularly words and sentences with different durations and spectra. In addition, following Derey et al [37] who showed the effect of the sound category (vocalizations, traffic sounds, or tones) and behavioral relevance (neutral versus fearful sounds with differential effects on behavior) on localization, the effect of the content's relevance and the speaker's familiarity to the listener should also be tested. An additional limitation of the present study is that the attenuation level of HPDs was measured generally, using a free-field microphone, and not individually for each participant; adding the measurement of individual attenuation levels as a predicting factor for localization would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Esta revisão foi conduzida conforme as recomendações PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) 16 . As análises foram realizadas pelo programa RevMan 5 ®.…”
Section: Protocolo E Registrounclassified
“…Table 2 presents known incompatibilities between HPD characteristics and those of the two other triad components and which were mainly gathered from a reference book [1] (see chapter 11) but also from the grey literature [66], research papers focusing on specific issues associated with HPD use [67][68][69] and a general survey on HPD use [70]. These incompatibilities can generate discomforts and thus lead to preferences for a given type of HPD, or in the worst case to the non-use of the HPD.…”
Section: Limitations Of Existing Behavioral Modelsmentioning
confidence: 99%
“…Earplugs are preferred by individuals favoring discrete hearing protectors and/or concerned with their hairstyle [1] Earmuffs can be difficult to wear in hot environments [1,67,68] Over-attenuating HPDs can block important environmental sounds such as alarm signals, machine sound and colleagues' speech [1] Earmuffs reduce the localization of the noise sources more than earplugs [69] HPD/Work environment Earplug insertion and removal can be time consuming and incompatible with work tasks when many removals are required during the work shift (and thus, earmuff are preferred in this case [1,70]) Earmuffs can interfere with movements when work is carried out in a tight space [1] Compared to earmuffs, earplug efficiency is more dependent on user training, skill and motivation [1] HPD requiring a periodic re-positioning is not adapted to work tasks based on a fast pace of repetitive movements [71] 1.…”
Section: Hpd/personmentioning
confidence: 99%